Clinico3hemodynamic features of arterial hypertension in patients with metabolic syndrome - L. I. Gapon; I. A. Zhevagina; T. I. Petelina; V. A. Kalinina (Российский кардиологический журнал)
The trial included 56 patients (mean age 51.8 ± 0. 8) with metabolic syndome (MS): arterial hypertension - AH (mean stage of AH 11.45 ± 1.1 yrs), non-insuline-dependent diabetes mellitus (mean stage 6. 7+0. 7 yrs), abdominal adiposity, and dyslipidemia. The control group consisted of 22 patients (mean age 49.27 ± 1.78) without metabolic abnormalities. 24-hour BP monitoring was performed in both groups. AH patients with MS demonstrated abnormalities in daily profile of heart rate (HR) and double product (DP, BPx HR/100) during all temporal intervals (whole day, day- and nighttime). This enhanced hemodynamic load on the heart and facilitated progression of left ventricular myocardial hypertrophy (LVMH). Advanced stage of high BP made MS more severe: Stage III AH patients with MS demonstrated significantly greater increase in systolic BP (SBP) (whole day, day- and nighttime) and SBP variability (whole day, day- and nighttime). Therefore, AH is an important factor in MS pathogenesis and progression.